The Effect of Previous Crop on Different Forage Crops in Summer Sowing - MUHCU, Berat; YILDIRIM, İlknur and KARDEŞ, Yusuf Murat and GÜLÜMSER, Erdem (MAS Journal of Applied Sciences, 2023)
This study was carried out to determine the hay yield and quality traits of silage mazie (Zea mays L.), sorghum sudangrass hybrid (Sorghum bicolor x Sorghum sudanense Stapf.) and buckwheat (Fagopyrum esculentum L.) sowing under alfalfa and oats in Pazaryeri district of Bilecik province in 2023. The study was designed according to the Random Block Trial Design with 3 replications and each plant was evaluated on its own. The hay yield (HY), crude protein ratio (CP) and yield (CPV), acid detergent fiber (ADF), neutral detergent fiber (NDF), potassium (K), phosphorus (P), calcium (Ca), and magnesium (Mg) ratios were determined. The highest HY and CPV in three plants of of were obtained from plots planted after alfalfa. According to the results, silage maize, sorghum sudangrass hybrid and buckwheat grown after alfalfa showed better performance in terms of the examined traits. Accordingly, it has been determined that it would be more appropriate to plant all three plants after alfalfa as summer crops in the ecology of the region.